Graphene- and Graphite Oxide-Reinforced Magnesium Oxychloride Cement Composites for the Construction Use - Lauermannová, Anna-Marie; Lojka, Michal; Pavlíková, Milena; Pivák, Adam; Záleská, Martina; Pavlík, Zbyšek; Zmeškal, Oldřich; Jankovský, Ondřej (University of Chemistry and Technology, Prague, 2021)
Graphene and graphite oxide reinforced magnesium oxychloride cement (MOC) pastes were researched. To produce MOC pastes, the light-burnt magnesium oxide was added and dispersed in the magnesium chloride solution. The graphene powder, graphite oxide powder, and their combination were incorporated in the solution. The total amount of the nano additives was 0.5 % by the weight of the magnesium oxychloride binder. The morphology and microstructure of the hardened materials were studied using scanning electron microscopy (SEM). The phase composition of precipitated MOC-based products was investigated using X ray diffraction (XRD). The macrostructural parameters of the composites such as bulk density, specific density, and open porosity were evaluated. Mechanical strength and stiffness were analyzed by the measurement of flexural and compressive strength and dynamic elastic modulus. The electrical properties were examined by the use of impedance spectroscopy (IS). From the experimental results the model of the transport of electric charge in researched materials dispersion was estimated. The use of graphene- and graphite oxide-reinforcement of MOC matrix gave highly dense materials of low porosity, high mechanical resistance, whereas the used nano-additives enabled the produce of composites of high strength efficiency index. The addition of graphene particles and the formation of graphite agglomerates significantly decreased electrical resistivity of the MOC matrix which was originally characterized by low electrical conductivity.

Graphene and graphite oxide reinforced magnesium oxychloride cement (MOC) pastes were researched. To produce MOC pastes, the light-burnt magnesium oxide was added and dispersed in the magnesium chloride solution. The graphene powder, graphite oxide powder, and their combination were incorporated in the solution. The total amount of the nano additives was 0.5 % by the weight of the magnesium oxychloride binder. The morphology and microstructure of the hardened materials were studied using scanning electron microscopy (SEM). The phase composition of precipitated MOC-based products was investigated using X ray diffraction (XRD). The macrostructural parameters of the composites such as bulk density, specific density, and open porosity were evaluated. Mechanical strength and stiffness were analyzed by the measurement of flexural and compressive strength and dynamic elastic modulus. The electrical properties were examined by the use of impedance spectroscopy (IS). From the experimental results the model of the transport of electric charge in researched materials dispersion was estimated. The use of graphene- and graphite oxide-reinforcement of MOC matrix gave highly dense materials of low porosity, high mechanical resistance, whereas the used nano-additives enabled the produce of composites of high strength efficiency index. The addition of graphene particles and the formation of graphite agglomerates significantly decreased electrical resistivity of the MOC matrix which was originally characterized by low electrical conductivity.
Graphene- and Graphite Oxide-Reinforced Magnesium Oxychloride Cement Composites for the Construction Use
Keywords: Graphene; Composites; Magnesium oxychlorides; Multiwalled Carbon Nanotubes; metal-Ionsmechanical-Properties; doped Graphene; silica Fume; adsorption; phase; water; reduction; hydration; Graphene; Composites; Magnesium oxychlorides; Multiwalled Carbon Nanotubes; metal-Ionsmechanical-Properties; doped Graphene; silica Fume; adsorption; phase; water; reduction; hydration